1994
DOI: 10.1029/94gb01044
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Global Carbon Cycle: Nitrogen fertilization of the terrestrial biosphere and the “missing” CO2 sink

Abstract: The discrepancy between estimates of net terrestrial CO2 emissions derived from (1) inverse modeling of the ocean/atmosphere system and (2) modeling of land use change, better known as the "missing" CO2 sink, suggests that some changing environmental factor, such as CO2, anthropogenic N emissions, or climate, has fertilized terrestrial ecosystems. To address this question, we herein describe and apply GLOCO, a global carbon cycle model. GLOCO's ocean submodel combines a box diffusion model with representations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(70 citation statements)
references
References 92 publications
7
62
0
1
Order By: Relevance
“…The remaining C flux was assumed to represent the perturbation of the terrestrial biosphere, including both net emissions from land use change and uptake from fertilization. Using GLOCO's terrestrial submodel to account for land use change, Hudson et al (1994) inferred that significant fertilization must have occurred. The modelled response to historical increases in CO # and temperature accounted for 31 % of the fertilization, implying that N fertilization must account for the rest.…”
Section: Modelling Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining C flux was assumed to represent the perturbation of the terrestrial biosphere, including both net emissions from land use change and uptake from fertilization. Using GLOCO's terrestrial submodel to account for land use change, Hudson et al (1994) inferred that significant fertilization must have occurred. The modelled response to historical increases in CO # and temperature accounted for 31 % of the fertilization, implying that N fertilization must account for the rest.…”
Section: Modelling Approachesmentioning
confidence: 99%
“…Gifford et al (1996) concluded that the assumption about how the exogenous N is initially taken up is a critical one that should be further investigated. Hudson, Gherini & Goldstein (1994) employed a very different approach to the calculation of Nstimulated C storage. The historical record of atmospheric CO # concentration was deconvoluted using the historical record of fossil fuel emission and the ocean submodel of their global C cycle model (GLOCO) for the period 1850-1985.…”
Section: Modelling Approachesmentioning
confidence: 99%
“…Global warming could increase decomposition and nitrogen mineralization and thereby the primary production, especially in the northern latitudes [Rastetter et al, 1991;Hudson et al, 1994]. This temperature feedback could possibly offset the increased CO 2 releases from the northern soils (temperature feedback on soil respiration).…”
Section: % Of the Potential With Unlimited Nutrients [Comins Andmentioning
confidence: 99%
“…More recent estimates of the carbon sink caused by anthropogenic N deposition range from 0.50 to 1.50 Pg yr-' (Kohlmaier et al 1988, Hudson et al 1994, Schindler and Bayley 1993, Townsend et al 1996. Hudson et al (1994) The analysis of atmospheric C02 and 613C has provided another perspective on the global carbon cycle and has allowed a more robust determination of the latitudinal distribution of net terrestrial C02 exchange (e.g., Ciais et al 1995a; see also Section 2.2).…”
Section: Relation Of This Study To Other Analysesmentioning
confidence: 99%
“…Hudson et al (1994) The analysis of atmospheric C02 and 613C has provided another perspective on the global carbon cycle and has allowed a more robust determination of the latitudinal distribution of net terrestrial C02 exchange (e.g., Ciais et al 1995a; see also Section 2.2). The latitudinal distribution of the carbon sink derived from N deposition is similar to the latitudinal distribution derived from isotopickoncentration measurements coupled to an inverse modeling framework ( Fig.…”
Section: Relation Of This Study To Other Analysesmentioning
confidence: 99%